2016
DOI: 10.1016/j.aquatox.2015.11.017
|View full text |Cite|
|
Sign up to set email alerts
|

Carbendazim exposure induces developmental, biochemical and behavioural disturbance in zebrafish embryos

Abstract: Carbendazim is a widely used broad spectrum benzimidazole fungicide; however, its effects to non-target aquatic organisms are poorly studied. The aim of this study was to investigate the toxic effects of carbendazim to zebrafish early life stages at several levels of biological organization, including developmental, biochemical and behavioural levels. The embryo assay was done following the OECD guideline 236 and using a concentration range between 1.1 and 1.8mg/L. Lethal and developmental endpoints such as ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 56 publications
3
30
0
6
Order By: Relevance
“…A similar fact occurred with LDH, a key enzyme in the anaerobic pathway of energy production. LDH acts as a cell injury marker at tissues, particularly when high levels of energy are required in a short period of time as in case of chemical stress conditions [42,[44][45][46]. In the present work, AMX significantly inhibited LDH, which may indicate a decreased glycolytic capacity in zebrafish larvae or suggest cellular necrosis leading to enzyme leakage and/or enzyme inhibition [45].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…A similar fact occurred with LDH, a key enzyme in the anaerobic pathway of energy production. LDH acts as a cell injury marker at tissues, particularly when high levels of energy are required in a short period of time as in case of chemical stress conditions [42,[44][45][46]. In the present work, AMX significantly inhibited LDH, which may indicate a decreased glycolytic capacity in zebrafish larvae or suggest cellular necrosis leading to enzyme leakage and/or enzyme inhibition [45].…”
Section: Discussionsupporting
confidence: 49%
“…Considering that GST is an enzyme that plays an important role in phase II of the detoxification process, responsible for the biotransformation of xenobiotic compounds and acts a marker of antioxidant mechanisms [42][43][44][45], our results showed that AMX inhibited the detoxification process and the antioxidant activity in the embryonic stage of zebrafish. A similar fact occurred with LDH, a key enzyme in the anaerobic pathway of energy production.…”
Section: Discussionmentioning
confidence: 76%
“…The total distance was the statistically analyzed parameter and it consisted of the total swimming distance of the larvae during each measurement period. The methodology followed here was based on a previously described protocol …”
Section: Methodsmentioning
confidence: 99%
“…Increases in ChE activity in D. magna exposed to low concentrations of cadmium and the carbamate propoxur have been reported (Printes and Callaghan ; Jemec et al ), which could have been related to compensatory mechanisms following the disruption of homeostasis (Calabrese and Baldwin ). Andrade et al () observed an increase in ChE activity after exposure of zebrafish ( Danio rerio ) embryos to carbendazim, which the authors hypothesized to be related to apoptosis mechanisms; Jiang et al () found that this increase was associated with the induction of gene expression related to apoptosis. Even though the exact mechanisms are not yet understood, Jiang and Zhang () have theorized that ChE participates in the regulation of apoptosis and cell proliferation.…”
Section: Resultsmentioning
confidence: 99%